2020
DOI: 10.1128/mbio.03260-19
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa Lectin LecB Causes Integrin Internalization and Inhibits Epithelial Wound Healing

Abstract: The opportunistic bacterium Pseudomonas aeruginosa produces the fucose-specific lectin LecB, which has been identified as a virulence factor. LecB has a tetrameric structure with four opposing binding sites and has been shown to act as a cross-linker. Here, we demonstrate that LecB strongly binds to the glycosylated moieties of ␤1-integrins on the basolateral plasma membrane of epithelial cells and causes rapid integrin endocytosis. Whereas internalized integrins were degraded via a lysosomal pathway, washout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 57 publications
3
52
0
3
Order By: Relevance
“…Lectins are proteins on the outer membrane of P. aeruginosa, which recognize glycosylated carbohydrates on host tissues, aiding the adherence of bacterial cells. For example, LecA (which binds to galactose) and LecB (which binds to fucose) mediate the adherence of this pathogen to epithelial cells in the lung [51,52]. These cell-mediated virulence determinants have important roles in the initial phase of colonization, persistence, and in the establishment of infections in vivo [53].…”
Section: Virulence Factors Of P Aeruginosamentioning
confidence: 99%
See 1 more Smart Citation
“…Lectins are proteins on the outer membrane of P. aeruginosa, which recognize glycosylated carbohydrates on host tissues, aiding the adherence of bacterial cells. For example, LecA (which binds to galactose) and LecB (which binds to fucose) mediate the adherence of this pathogen to epithelial cells in the lung [51,52]. These cell-mediated virulence determinants have important roles in the initial phase of colonization, persistence, and in the establishment of infections in vivo [53].…”
Section: Virulence Factors Of P Aeruginosamentioning
confidence: 99%
“…Biofilm formation is a critical attribute of P. aeruginosa in being a successful nosocomial pathogen and it is also an important hallmark of chronic bacterial persistence. This may be observed in dental caries on the tooth surfaces [85,86], in skin and soft tissue infections [52], in infections of the middle ear [87], catheter-associated infections [19], pneumonia, and in the lungs of CF patients [88]. In the latter case, P. aeruginosa is able to survive and avoid clearance (withstanding the immune response and the subsequent administration of antimicrobials) in the respiratory and conductive zone of the lungs [89,90].…”
Section: Biofilm Formationmentioning
confidence: 99%
“…A recent study reported that LecB binds to the side chain of Psl and help stabilize the biofilm matrix [ 138 ]. LecB is also implicated in the reduction of tissue healing [ 139 , 140 ].…”
Section: Cell Appendages and Adhesinsmentioning
confidence: 99%
“…The flagellum interacts with Toll-like receptors TLR-5 and TLR-2 [125,126], mucins [127] and heparan sulfate proteoglycans [122,128], while the pili bind to N-glycans [129]. Furthermore, P. aeruginosa interacts with laminin [130,131] and integrins [132][133][134]. Both the pili and the flagellum recognize asialo-monogangliosides (GM1 or GM2), which expose a GalNAcβ1-4Gal moiety [64].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%